Penganggaran Partisipatif dan Kinerja : Dimediasi oleh Self Efficacy - Siti Samsiah; Della Hilia Anriva; Restu Agusti; Jeny Monika Putri (Akuntansi & Ekonomika, 2021)
This study aims to find evidence that there is an effect of participatory budgeting with the performance of the Pekanbaru City Dinas Pekerjaan Umum Dan Penataan Ruang mediated by self-efficacy. In order to support the research evidence, the researchers distributed to the employees of the Pekanbaru City PUPR Office the number of research samples was 122 employees. The hypothesis with Partial Least Square SmartPLS 3 software shows evidence that participatory budgeting and self-efficacy have an influence on managerial performance testing, so the relationship between participatory budgeting also has an effect on self-efficacy. Further hypothesis testing evidence states that self-efficacy does not have a mediating role in the relationship between participatory budgeting and managerial performance.